Improving Reading Skills of Dyslexic Students in Remote Areas Through a Multisensory Alphabet Wheel Intervention - Dahlan, Amirullah; Suparno (UNDIKMA, 2025)
This study examines the effectiveness of a multisensory intervention using an alphabet-wheel medium to enhance the reading skills of dyslexic primary school students in a remote 3T (frontier, outermost, underdeveloped) region. Employing a Single Subject Research (SSR) A-B-A design, the research was conducted with a third-grade dyslexic student at SDN 001 Muara Ancalong, East Borneo. The intervention integrated visual, kinesthetic, and tactile stimuli to overcome phonological and visual processing barriers commonly experienced by dyslexic learners. Structured oral tests focusing on syllabic patterns (CV, VCV, CVCV) were administered across 12 sessions, and data were analyzed using descriptive statistics and visual analysis within and across phases. Findings revealed significant improvement; mean reading accuracy increased from 46.62% in the first baseline to 62.96% during intervention and reached 72.83% in the second baseline. Furthermore, learning independence improved, as the proportion of tasks completed without assistance rose from 20% to 65%. The results demonstrate that simple, low-cost alphabet-wheel media can effectively support reading skill development and foster independence in dyslexic learners in resource-limited settings. This study highlights the potential of context-sensitive multisensory approaches to address learning barriers, particularly in underserved regions, and recommends broader teacher training and policy integration of multisensory methods as inclusive education strategies.